A Review, Half a Century Later (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
In the text we offer a re-reading of the book La torre di Babele (The Tower of Babel), 1967, by Ludovico Quaroni, in order to try and understand, fifty years after its publication, whether the theses proposed by its author are still, at least partially, valid and effective. As is common knownledge, since 1967 the conditions of the city have changed radically, and this might imply that Quaroniâ€™s theses are outdated. In fact, the book touching on the basic themes of urban development, it contains numerous arguments that are still relevant, as well as insights that would be of considerable interest were they developed further. Beginning with some hypotheses from his book regarding Quaroniâ€™s teaching activities we will try to analyze the complex introduction by Aldo Rossi, beyond the Milanese architectâ€™s appreciation for the authorâ€™s theses. The recurring themes in the text are then summarized, animated by the desire to seek a new and more complex unity between architecture and urban planning. Â